ANALISIS PENGGUNAAN KOHESI GRAMATIKAL PADA TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 5 BOGOR - Tri Mahajani; Suhendra Suhendra; Nita Nurlihayati (Universitas Pakuan, 2021)
ANALYSIS OF THE USE OF GRAMMATICAL COHESION IN THE EXPLANATION TEXT OF CLASS VIII SMP NEGERI 5 BOGORThe aim of this research is to describe the use of grammatical cohesion of references and substitutions in students' explanatory texts. The focus of this research is the use of grammatical cohesion tools in the form of references and substitutions in students' explanatory texts. The method used in this research is qualitative descriptive, meaning that the data found in the form of sentences and will be described descriptively. Data sources used in this research are 29 explanatory texts for students of class VIII H of SMP Negeri 5 Bogor, using literature study data collection techniques. Grammatical cohesion tools analyzed in the explanatory text are references and substitutions. From the results of this analysis found the use of reference grammatical cohesion and substitution tools of 80 data findings. The most findings are the use of references as much as 67 data (84%). References usually relate to elements that are referring and referenced. The references are inside and outside the text with the most findings being personal and demonstrative references. Then the use of substitution grammatical cohesion only found 13 data findings (16%). This substitution is related to the substitution of a language element with other language elements. Grammatical cohesion of substitution is very little used by students in explanatory texts. This happens because of the lack of understanding of students in writing texts in accordance with good linguistic rules and the lack of vocabulary that students have. However, from this amount it can be concluded, this explanatory text of eighth grade students of SMP Negeri 5 Bogor has many uses of grammatical cohesion. The results of this research give a positive thing on learning Indonesian, especially aspects of language in school.